Born into Brothels - Briski, Zana; Kauffman, Ross (United States : Red Light Films, 2004)
Academy award-winning documentary Born into Brothels is a touching portrait of Calcutta’s red light district children. Facing abject poverty, abuse and despair, these children have little possibility to escape the fate of their mothers. The film chronicles the lives of eight children born in brothels and director Zana Briski's determination to teach them photography. What develops is much more than pictures.
Keywords: Documentary films